1988
DOI: 10.1136/bmj.296.6635.1498
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight and risk of high blood pressure in adulthood

Abstract: Hospital birth records were sought for 104 men from a pool of male army conscripts with "normal" or "high" blood pressure when measured at 28 years of age. Of 77 men whose birth weight and date of the mother's last menstrual period before the pregnancy could be found, 25 had a resting diastolic blood pressure of ¢90 mm Hg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(89 citation statements)
references
References 18 publications
5
83
1
Order By: Relevance
“…1,[21][22][23] Other studies have demonstrated only a weak 24 or no significant support of this association. 25 In a recent analysis of follow-up data, Hack et al 26,27 reported lower blood …”
Section: Discussionmentioning
confidence: 99%
“…1,[21][22][23] Other studies have demonstrated only a weak 24 or no significant support of this association. 25 In a recent analysis of follow-up data, Hack et al 26,27 reported lower blood …”
Section: Discussionmentioning
confidence: 99%
“…30 This was followed by a number of observations of a negative association between birthweight and blood pressure. [31][32][33][34] Researchers led by Barker then discovered a link between birthweight and risk of cardiovascular disease more generally. [35][36][37][38] Since then, additional findings have evolved into the "Developmental Origins of Health and Disease" hypothesis, which states that during critical periods of prenatal and postnatal mammalian development, nutrition and other environmental stimuli can influence developmental pathways, thereby inducing permanent changes in metabolism and chronic disease susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, several human studies have shown that birth weight is inversely associated with blood pressure in childhood, as well as in adult life (8)(9)(10)(11)(12)(13)(14), but this association has not been confirmed by all investigators (15)(16)(17). In their experimental studies, Langley and co-workers (18) showed that rats exposed to a low-protein diet in utero exhibited lower body weight at birth and higher systolic blood pressure at 4 weeks of age.…”
Section: Introductionmentioning
confidence: 94%